Optimalisasi Kolam Ikan Untuk Pemenuhan Gizi Santri - Nurdeni Nurdeni; Endah Diah Parwati; Ririn Regiana Dwi Satya; Haryanto Haryanto; Muhammad Syahiddin; Dian Novita Susanto (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Pesantren in Indonesia today have a wide variety of activities, apart from the main program, namely learning and teaching activities, but also farming and/or livestock activities in order to utilize school land and as an effort to fulfill daily needs for the scope of the pesantren itself and in order to support food security. Catfish farming is one way to be able to teach animal husbandry skills to students by utilizing land in the form of fish ponds that are not functioning optimally. The catfish farming is also expected to be utilized further so that it becomes an additional source of income for all school parties. This community service program is carried out with educational methods and catfish breeding practices by utilizing water sources that are widely available around the school. In the end, this activity can be used as a food security program and can also function as an additional source of income for schools.